Economia solidária e política pública de geração de trabalho e renda – uma análise do Programa Bolsa Trabalho do estado do Pará - SILVA, Leny da Gama e (Universidade Federal do Pará, 2013)
The dissertation is entitled "Solidarity economy and public policy to generate jobs and income: an analysis of the Bolsa of Pará Work" includes contributions from the proposal to include socially and economically excluded young workers in the formal labor market from a political strategy which articulated the solidarity economy, generating jobs and income and financial incentive temporary and conditioning. The survey was developed based on the experience of that program, conducted from 2007 to 2010, while government proposal who wrote the Public Policy Work and Income of the state, signaling the possible strategies for the construction of the fight against unemployment, poverty, social exclusion, especially of young people from the social economy. The Work Scholarship Program had three main social and professional qualification: professional training for the formal market, creation of individual and family development and organization of enterprises collective solidarity. For analytical purposes the research was defined in the latter axis, given their difference in promoting inclusive production through cooperative work and self-managing. Thus, he was elected a qualitative approach to realization of this dissertation combining documentary research on projects and reports related to Work Scholarship Program with the completion of an interview with engineers and technicians who participated in the program. In addition to research on books, dissertations, monographs and other productions on the policies discussed in this work. Tour the goal of this dissertation consists in analyzing the Work Scholarship Program, in its articulation of policies to transfer income, social economy and creating jobs, the survey results showed that the proposal to include socially and economically from this young workers strategy proves possible, however demand interaction with other social and economic policies of the country in relation to the social economy, because it is a new policy and how to organize the paper notes that failed mainly clarification of the proposal , demand for the beneficiary group and financing policies for implementation of the projects formed by the program.